Pewarisan Nilai Sejarah Sebagai Transmisi Memori Kolektif Masyarakat Baduy - Kusuma, Budi; Yulifar, Leli (Universitas Galuh, 2025)
This study explores the mechanisms of historical value transmission within the Baduy indigenous community as a form of collective memory transmission and cultural resistance to modernization. The primary aim of this research is to analyze how oral traditions, cultural practices, and social structures contribute to shaping collective consciousness and preserving community identity. A qualitative approach was employed using a library research method, utilizing various relevant literature sources as primary data. The findings indicate that the transmission of historical values in the Baduy society occurs through non-formal education patterns based on direct experience, social interaction, and ritual practices, with strong support from customary institutions and the role of women within the family. Resistance to formal education and modern technology is presented not as a sign of backwardness, but as a cultural strategy to maintain the integrity of values and identity. This study emphasizes the importance of historical value transmission as an active mechanism that shapes cultural continuity and provides social resilience for the community. Its implications include enriching the discourse on cultural preservation among indigenous communities through a deeper understanding of value transmission patterns grounded in oral traditions and everyday practices, as exemplified by the Baduy people, and serving as a basis for formulating more culturally responsive policies.